PH-Regulated lignin as a green catalyst for Highly-Efficient CO2 cycloaddition. (15th August 2023) - Ouyang, Yidan; Lei, Bin; Tan, Zhouqing; Hu, Fen; Wu, Zhao; Wang, Jiaxue; Ma, Yixuan; Zhang, Ran; Guo, Li; Chen, Feifei
Graphical abstract: Highlights: Lignin with sharply raised COOH/Ar-OH ratio (0.48) was obtained by acid up-grading. The pH-tuned lignin can greatly catalyze the CO2 cycloaddition under mild condition. Cracking of β-O-4′ and ester units caused the enriching of Ar-OH and COOH in lignin. Experimental and DFT study revealed the valid synergistic effect of –COOH and Ar-OH. Abstract: Lignin, one of the most abundant sources of renewable biomass on earth, has the potential to be used as an alternative and value-added green catalyst via the up-grading of lignin waste. However, the application of lignin-based catalysts is still a significant challenge due to the complexity of the lignin structure. Herein, lignin enriched with COOH and Ar-OH groups were generated after subjecting to the acid gradient grading method, and lignin with sharply raised COOH/Ar-OH ratio (0.48) was obtained when it was precipitated at pH 2. This up-graded lignin exhibited outstanding catalytic activity (Yield: 93 %, TON: 131) for the coupling reaction between styrene oxide (SO) and CO2 under mild condition (T: 120 ℃, P: 0.5 MPa). The 31 P NMR and 2D HSQC NMR analysis showed that enriching of Ar-OH and COOH groups was due to the cracking of the β-O-4′ interunits and ester units such as p -coumarates (PCA) and ferulates (FA) under acidic conditions. Particularly, the Ar-OH groups showed significant increase only under stronger acid condition (pH 1), while the COOH groups were constantly unleashed with the pH decreasing (pH from 3 to 1). Furthermore, the combined experiments and DFT study for a series of lignin model monomers catalysts revealed the outstanding synergistic promoting effect of COOH and Ar-OH in lignin on the conversion of CO2 and epoxides due to the declined energy barrier of the ring-opening step, while the synergistic effect could be weakened by –OCH3 in lignin. Thus, lignin waste can be converted into excellent catalyst for transforming CO2 into high-value chemicals by regulating their catalytic centres through the acid gradient grading method. The fundamental results in this work can also provide theoretical guidance for the design and development of green lignin-based catalysts in the future.